H2-boundedness of the pullback attractor for the non-autonomous SIR equations with diffusion. (January 2015) - Anguiano, María
Abstract: We prove some regularity results for the pullback attractor of a non-autonomous SIR model with diffusion in a bounded domain Ω of R d where d ≥ 1 . We show a regularity result for the unique solution of the problem. We establish a general result about H 2 ( Ω ) 3 -boundedness of invariant sets for the associate evolution process. Then, as a consequence, we deduce that the pullback attractor of the non-autonomous system of SIR equations with diffusion is bounded in H 2 ( Ω ) 3 .